Merancang dan membangun sistem IoT untuk pengamatan suhu dan kelembaban menggunakan DHT 22 dengan ThingSpeak - Fachrul Rizky Syaputra (Yayasan Kita Menulis - JoCPES, 2025)
In a study conducted in recent years, it was found that atmospheric conditions such as temperature and humidity values greatly affect the climatic conditions of a region. This real-time temperature and humidity monitoring system is very useful and can be used in various regions. By using IoT, monitoring can be done in real-time. Temperature and humidity can use DHT 22 linked to ESP 32 and the data is stored and displayed in ThingSpeak. The trial of the monitoring tool was carried out for more than 31 hours and obtained 6920 data. At the time of the experiment the monitoring system worked well. At the time of observation for temperature the maximum value is 32.4 ̊C, the minimum value is 28.1 ̊C, the mean is 29.75621387283237 ̊C, and the standard deviation is 3.587911994653761 and for humidity the maximum value is 81.4%, the minimum value is 63.6%, the mean is 72.6355404624 and the standard deviation is 3.5879112. From the experiment, it was also found that the temperature value was inversely proportional to the humidity and when it was going to rain the temperature value went up while the humidity went down and when it rained the temperature went up while the temperature went down.